Participatory research and gender analysis initiative = Iniciativa de análisis de género e investigación participativa - Biermayr Jenzano, Patricia (International Center for Tropical Agriculture, 2011)
The Participatory Research and Gender Analysis (PRGA) initiative aims to improve the competence of the CGIAR research programs and collaborating institutions in mainstreaming the use of gender-responsive participatory approaches. Mainstreaming a gender perspective is the process of assessing implications for women and men of any planned action, including legislation, policy, or program, in any area and at any level. It is a strategy for making women's, as well as men's, concerns and experiences an integral dimension of designing, implementing, monitoring, and evaluating policies and programs in all political, economic, and societal spheres so that women and men benefit equally, and inequality is not perpetuated. The ultimate goal is to achieve gender equality.